2021
DOI: 10.1038/s42003-020-01524-w
|View full text |Cite
|
Sign up to set email alerts
|

Substrate thermal properties influence ventral brightness evolution in ectotherms

Abstract: The thermal environment can affect the evolution of morpho-behavioral adaptations of ectotherms. Heat is transferred from substrates to organisms by conduction and reflected radiation. Because brightness influences the degree of heat absorption, substrates could affect the evolution of integumentary optical properties. Here, we show that vipers (Squamata:Viperidae) inhabiting hot, highly radiative and superficially conductive substrates have evolved bright ventra for efficient heat transfer. We analyzed the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…It is unclear what information these throat color signals contain and how much, if any, effect color variation in this body region has on heating and cooling rates. Previous work in reptiles has shown that ventral pigmentation has significant thermal effects on heating and cooling (Tanaka, 2007; Smith et al, 2016), and that differences in substrate thermal properties can influence ventral color evolution (Goldenberg et al, 2021). Throat color polymorphism has been associated with numerous trait deviations among the different color morphs in Podarcis lizards (Calsbeek et al, 2010; Abalos et al, 2016; Brock et al, 2020; Sreelatha et al, 2021), though its significance on thermoregulation remains understudied.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear what information these throat color signals contain and how much, if any, effect color variation in this body region has on heating and cooling rates. Previous work in reptiles has shown that ventral pigmentation has significant thermal effects on heating and cooling (Tanaka, 2007; Smith et al, 2016), and that differences in substrate thermal properties can influence ventral color evolution (Goldenberg et al, 2021). Throat color polymorphism has been associated with numerous trait deviations among the different color morphs in Podarcis lizards (Calsbeek et al, 2010; Abalos et al, 2016; Brock et al, 2020; Sreelatha et al, 2021), though its significance on thermoregulation remains understudied.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while the dorsum is exposed to both solar radiation and prey/ predator sight, the ventral region is mostly cryptic. The idea is supported by Azócar et al (2015) and Goldenberg et al (2021), who provided evidence that ventral, but not dorsal, brightness follows the Bogert's rule, likely to provide thermal benefits (warmer grounds in the tropics versus cooler grounds in the temperate zones) while the exposed region is selected by multiple competing interests including, but not limited to, camouflage and UV protection following Gloger's rule.…”
Section: Thermoregulation and Climate Changementioning
confidence: 94%
“…These physiological and morphological traits are often shaped by multiple competing interests, and, therefore, it is understandable why a unified rule cannot explain ecogeographical patterns for colour brightness across a vast taxonomic group. Indeed, there is evidence in the literature for both Gloger's and Bogert's (Ribot et al 2019, Goldenberg et al 2021), but those studies focus on a few or a group of closely related species, which were likely shaped by similar eco‐evolutionary pressures and dynamics. However, if the number of focal taxa changes or different focal species are selected, then often no patterns are found (Forsman 2011, Rosa and Saastamoinen 2020).…”
Section: Inconsistences Between Coloration and Body Size Rulesmentioning
confidence: 99%
“…Following the same hypothesis for terrestrial vertebrate groups may provide insight into why more thermal tolerant species such as reptiles do not have green or blue 22 autofluorescent scales or scutes unless they are marine dwelling species (Gruber and Sparks 2015) or blind snakes (Eipper et al 2020). While there is an outlying exception to this rule for reptiles, the ventral coloration of a noturnal desert gecko (Prötzel 2021), recent evidence shows that ventral coloration in ectotherms is influenced by thermal properties of the substrate in which they live (Goldenberg et al 2021), which may actually provide further evidence of thermal influence on the evolution of biofluorescence. Therefore, the origins of more ancient green and blue autofluorescence may have evolved as a visual function for species which were driven to low-light, thermally regulated environments due to an intolerance of the extreme climate conditions surrounding the MMCO.…”
Section: Predictions For Evolution Of Biofluorescence and Current Hyp...mentioning
confidence: 99%